Reinventing Informal Activities through Placemaking for Community Resilience: Maguwoharjo International Stadium, Sleman - Anggraini, Stefy Prasasti; Saptorini, Hastuti; Juliani, Any (Departement of Architecture, Universitas Islam Indonesia, 2025)
The degradation of life due to the COVID-19 pandemic, whether physiological, psychological and economic, requires a comprehensive thought on community resilience according to the capacity and context. The placemaking experiences in The Maguwoharjo International Stadium (MIS) area indicates a positive community response through sports, recreation, and informal businesses than enliven the area. This study aims to strategies for reinventing existing activities using a placemaking approach, specifically through three variables, the Person, Procedures and Place. The hope is that when the MIS area is designed and developed as a Tourism Special Economic Zone (SEZ), these actors remain included a development stakeholder. This study using qualitative descriptive methods and categorized into primary and secondary activities in public spaces. The results highlight three points: alignment of MIS with MICE-based tourism policy, the importance of placemaking for physical resilience and informal business, and the need for landscape element to mitigate pollutants.